Pathogenic potentiality of fungi associated with the seeds of different cotton (Gossypium hirsutum L.) varieties in Bangladesh (Dhaka University Journal of Biological Sciences, 2020)
A total of 24 species of fungi, namely Aspergillus flavus Link, A. fumigatus Fresenius, A. niger (Type 1 and Type 2) Van Tiegh, A. ochraceus K. Wilhelm, A. nidulans Eidam, Aspergillus sp.1, Aspergillus sp.2, Aspergillus sp.3, Curvularia lunata (Wakker) Boedijn, Colletotrichum gloeosporioides Penz & Sacc, C. gossypii Southw., Chaetomium globosum Kunze., Fusarium nivale (Fr.) Sorauer, F. moniliforme J. Shelden, F. oxysporum Schlechtendal, F. fujikuroi Nirenberg, Mucor sp. P. Micheli ex L., Penicillium sp.1 and sp.2 Link, Rhizoctonia solani Khun., Rhizopus stolonifer (Ehrenb.) Vuill., Rhizomucor sp. Lucet & Costantin, Syncephalastrum racemosum Cohn and Trichoderma viride Pers. were found to be associated with the seeds of 14 varieties (CB 1- CB 14) of cotton. Out of these 24 fungal species, nine were found to be pathogenic to cotton. They were Aspergillus flavus, A. niger (Type 1), Aspergillus sp. 1, Colletotrichum gloeosporioides, Curvularia lunata, Fusarium nivale, F. moniliforme, Mucor sp. and Rhizoctonia solani. These pathogenic fungi had remarkable effect on seed germination, vigor index, root-shoot length and mortality of cotton seedlings. The germination percentage of control seeds was 88 but because of the presence of pathogenic fungi the rate showed considerable reduction in all the varieties and it varied from 20 to 82%. Among the nine fungal isolates Rhizoctonia solani showed maximum reduction in seed germination. Aspergillus flavus, Colletotrichum gloeosporioides and Fusarium moniliforme also caused near about 50% reduction in seed germination. Mortality percentage of control seedling were also less (6) whereas, in inoculated seeds it was higher and varied from 7 - 23%. Root- shoot ratio of control seedlings was high but less in inoculated seedlings. The vigor index of control plant was high (1548.8) but less in inoculated plants. The lowest vigor index was noticed for Rhizoctonia solani (202.0) and highest for Aspergillus sp. 1(1213.6). Results indicated that Curvularia lunata and Rhizoctonia solani showed a greater impact in reduction of cotton seed germination and vigor index.Dhaka Univ. J. Biol. Sci. 29(1): 107-115, 2020 (January)